Morphological development and cytochrome c oxidase activity in Streptomyces lividans are dependent on the action of a copper bound Sco protein - Blundell, Katie L. I. M. (The Royal Society, 2013)
Copper has an important role in the life cycle of many streptomycetes, stimulating the developmental switch between vegetative mycelium and aerial hyphae concomitant with the production of antibiotics. In streptomycetes, a gene encoding for a putative Sco-like protein has been identified and is part of an operon that contains two other genes predicted to handle cellular copper. We report on the Sco-like protein from Streptomyces lividans (Sco(Sl)) and present a series of experiments that firmly establish a role for Sco(Sl) as a copper metallochaperone as opposed to a role as a thiol-disulphide reductase that has been assigned to other bacterial Sco proteins. Under low copper concentrations, a Δsco mutant in S. lividans displays two phenotypes; the development switch between vegetative mycelium and aerial hyphae stalls and cytochrome c oxidase (CcO) activity is significantly decreased. At elevated copper levels, the development and CcO activity in the Δsco mutant are restored to wild-type levels and are thus independent of Sco(Sl). A CcO knockout reveals that morphological development is independent of CcO activity leading us to suggest that Sco(Sl) has at least two targets in S. lividans. We establish that one Sco(Sl) target is the dinuclear Cu(A) domain of CcO and it is the cupric form of Sco(Sl) that is functionally active. The mechanism of cupric ion capture by Sco(Sl) has been investigated, and an important role for a conserved His residue is identified.